Intradialytic Parenteral Nutrition in Pediatrics - Marisa Danielle Juarez (Frontiers Media S.A., 2018)
Children with end-stage renal disease (ESRD) on hemodialysis are at increased risk for malnutrition. Aggressive nutrition intervention such as intradialytic parenteral nutrition (IDPN) should be considered to prevent further co-morbidities and mortality associated with malnutrition when other interventions fail. IDPN is a non-invasive method of providing nutrition to malnourished hemodialysis (HD) patients via the HD access throughout the HD treatment. Although the evidence on the long-term benefits of IDPN is scant in pediatrics, there is evidence that it improves metabolic parameters and nutritional status. In this paper, therapy with IDPN including indications, goals of therapy, and elements to monitor will be described. In addition, a practice guideline for prescribing IDPN is provided.